2012
DOI: 10.1159/000343295
|View full text |Cite
|
Sign up to set email alerts
|

Premature Aging of the Microcirculation in Patients with Advanced Chronic Kidney Disease

Abstract: Background: Increasing age and advanced chronic kidney disease (CKD) are both associated with an attenuated vasodilator response of the skin microcirculation. In the present study, we investigated the effect of aging on microvascular reactivity in patients with advanced CKD. Methods: Acetylcholine (ACh)-mediated endothelium-dependent vasodilation and sodium nitroprusside (SNP)-mediated endothelium-independent vasodilation were assessed by iontophoresis combined with laser Doppler flowmetry. Microvascular funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…26 Chronic kidney disease may also contribute to premature aging of microcirculation. 27 Diabetes mellitus was present in 91 (45.5%) patients in the current study. It had been well known that the reduction of vessel density is correlated to the severity of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…26 Chronic kidney disease may also contribute to premature aging of microcirculation. 27 Diabetes mellitus was present in 91 (45.5%) patients in the current study. It had been well known that the reduction of vessel density is correlated to the severity of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 48%
“…A prior OCTA study has demonstrated that aging is associated with decreased vessel density in both the superficial and deep capillary plexus in the normal population . Chronic kidney disease may also contribute to premature aging of microcirculation . Diabetes mellitus was present in 91 (45.5%) patients in the current study.…”
Section: Discussionmentioning
confidence: 49%
“…However, the difference that we found between patients with diabetes versus HCs and patients with CAP is similar to an observation we made in the past. We repeatedly demonstrated a reduction in ACh-mediated vasodilatory response of approximately 300 to 400% points in several disease entities: hypertension (33), chronic kidney disease (34), and systemic sclerosis (35). We defined such a reduction as clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Data in patients with CKD are controversial. Thang et al [46] found that Ach and SNP iontophoresis provoked vasodilatation was altered in patients with advanced CKD compared to healthy controls. In contrast, Cupisti et al [47] found no alternations in the hyperaemic response after Ach and SNP iontophoresis in patients with CKD compared to healthy controls.…”
Section: Iontophoresismentioning
confidence: 99%